Teaching, learning, and leading with computer simulations - Qian, Yufeng, 1967- (Advances in educational technologies and instructional design., 2020)
""This book examines the recent advancement of simulation technology and explores the innovative ways that advanced simulation programs are used to enhance and transform teaching and learning"--Provided by publisher"--